1999
DOI: 10.1097/00003072-199903000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interoperator Variations in Region-of-Interest Drawing and Their Effect on the Measurement of Glomerular Filtration Rates

Abstract: Spatial reproducibility in ROI drawing does not necessarily relate directly to the associated quantitative reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 6 publications
0
22
1
Order By: Relevance
“…In contrast to some studies, which have reported signifi cant variations [11][12][13] , this study did not show any statistically signifi cant difference in the estimated values from manually drawn reigions of interest among the three experienced technologists, indicating that the nuclear medicine procedures studied are reproducible and operator independent. This may be because the commercial packages for image processing have become more advanced and easy to use and the technologists more familiar and skillful in digital image processing.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to some studies, which have reported signifi cant variations [11][12][13] , this study did not show any statistically signifi cant difference in the estimated values from manually drawn reigions of interest among the three experienced technologists, indicating that the nuclear medicine procedures studied are reproducible and operator independent. This may be because the commercial packages for image processing have become more advanced and easy to use and the technologists more familiar and skillful in digital image processing.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study does, however, represent one of the largest single-center, prospective studies analyzing resection and survival outcomes of 5-ALA FGS for newly diagnosed GBM in North America using a validated, semiautomated tumor segmentation method. Most studies to date, have used linear diameter or manual segmentation for this end, both of which are heavily user-biased and subject to inaccuracies [30, 36, 38-39, 42]. Lastly, using precision segmentation, this study demonstrates the impact that morphological tumor features (SA, SAVR, and NV%) have on resection and survival outcomes.…”
Section: Discussionmentioning
confidence: 76%
“…Some automated digital-image segmentation techniques have shown promise in measuring pre-operative tumor volumes, but few are designed to evaluate RTV where T1-hyperintense blood products (methemoglobin) and cavity collapse obscure measurements [40-41]. Such structural nuances can be accounted for using manual image contouring; however, this process is time-consuming and suffers from limited reproducibility [39, 42-44]. These limitations often lead to a resection being labeled as a “gross total resection” (GTR, with an RTV of predetermined volume) despite the presence of residual contrast-enhancement, potentially skewing endpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Radioisotope methods are accurate, and are known to have a high degree of reproducibility across different centers as long as computing algorithms are similar [29][30][31][32]. These methods have been recommended as routine by some authors [33], although their expense and logistics limit utilization in most centers.…”
Section: Discussionmentioning
confidence: 99%